Desenvolvimento da abordagem lean por meio de práticas de liderança : pesquisa-ação numa área de planejamento da produção - Pellegrino, Renato Arima (Universidade Federal de São Carlos, 2016)
Companies, to sustain their products’ competitiveness (cost, quality and time), need to maintain an improvement rate greater than the competitors, and not only possess good strategies, systems or technologies. The concept of "continuous improvement" has become increasingly popular in the business environment, and it is associated with a variety of approaches, and the lean manufacturing as one. Although the lean tools and methodologies are relatively easy to be implemented in different contexts, few companies can turn into real lean enterprises, since they have good results in the early stages of implementation, but fail in the long-term support. One of the key factors for sustaining lean approach is centered on the leadership role. This dissertation aims to develop, by performing an action research, the current leadership practices in a production planning area belonging to a company in the large industrial sector located in the State of São Paulo, and with a history of eight years working through the lean approach, to lean leadership model for the people development, in which are considerated the following factors: promoting employees self-development, people developing and training, and support daily kaizen. During the action research was possible to propose and evaluate the leadership practices to promote and support the implementation of lean approach. It was observed during the action research as a major challenge to reconcile operational routine of leaders and the team with the implementation of the lean principles and tools.
Keywords: Produção enxuta; Melhoria contínua; Práticas de liderança; Liderança; Liderança lean; Lean Manufacturing; Continuous Improvement; Leadership; Leadership Practices; Lean Leadership; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO